The magnitude of adherence to option B plus program and associated factors among women in eastern African countries: a systematic review and meta-analysis - Tsegaye, Reta (BMC Public Health, 2020)
BACKGROUND: Despite coverage and benefits associated with the prevention of mothers to child transmission (PMTCT) services, mothers’ adherence to option B plus is still a challenge. Though few primary studies are available on the magnitude of adherence to option B plus and factors associated in Eastern African countries, they do not provide strong evidence in helping policymakers to address suboptimal adherence to option B plus. Therefore, this systematic review and meta-analysis was intended to estimate the pooled magnitude of adherence to option B plus program and associated factors among women in Eastern African countries. METHODS: PubMed, Medline, HINARI, Cochrane library, the Web of Science, and Google Scholar were searched for studies reported on the magnitude of adherence to option B plus among women in Eastern African countries. The search terms used were “option B plus”, “magnitude”, “prevalence”, “PMTCT”, “ART adherence”, “associated factors”, “all lists of Eastern African countries” and their combination by Boolean operators. The effect sizes of the meta-analysis were the magnitude of adherence to option B plus and the odds ratio of the associated factors. STATA/SE V14 was used for statistical analysis, and publication bias was assessed using funnel plots and Egger’s test. RESULTS: Fourteen studies having total participants of 4883 were included in the systematic review and meta-analysis. Using the random effect model, the pooled prevalence of adherence to option B plus was 71.88% (95% CI: 58.54–85.23%). The factors associated with good adherence to option B plus PMTCT program were partner support (Adjusted odds ratio (AOR) = 4.13; 95% CI: 2.78–6.15), received counseling services (AOR = 4.12, 95% CI: 2.81–6.02), disclosure of HIV status to partner (AOR = 4.38; 95% CI: 1.79–10.70), and clinical stage of HIV/AIDS I/II (AOR = 2.62; 95% CI: 1.53–4.46). CONCLUSION: The level of adherence to option B plus program in Eastern African countries was generally sub-optimal. Thus, a coordinated effort is needed to raise the number of mothers to be tested, and early treatment initiation for HIV positive mothers before the disease advances. Furthermore, counseling services for couples on the importance of early treatment initiation and adherence to medications must be given due attention.